Economic Recovery Strategy for the SMEs Post Covid-19 Pandemic in Ponorogo: The Role of the Penta Helix Model - Dhika Amalia Kurniawan; Muhammad Ridlo Zarkasyi; Budi Setyanta (Universitas Muhammadiyah Sorong, 2023)
This study aims to develop a Penta helix collaboration strategy for SMEs in Ponorogo. The research method used in this research is qualitative with data collection through interviews, surveys, and observations. This study indicates that to develop sustainable SMEs, necessary to involve elements that play and contribute equally in developing the competitiveness of sustainable SMEs. Ponorogo needs to apply the Penta helix strategy in planning, implementing, and developing SMEs. The strategies that need to be carried out by the Penta helix elements involved are 1) The Government of Ponorogo needs to provide training and business assistance on an ongoing basis and provide convenience for MSMEs in terms of business legality. 2) Academics play a role as companions for MSME development and resource persons in business managerial training, 3) The media plays an active and sustainable role in publicizing and promoting MSME products so that they can be known by the wider community. 4) The Ponorogo community can play a role in assisting the right marketing strategy according to the problems faced by each MSMEs, and are also active in consuming MSMEs products. 5) Industry and business people play a role as partners who foster MSME product opportunities in facing competition by collaborating in the fields of training, marketing and assisting in building partnership networks.